A Wearable Microneedle-Based Extended Gate Transistor for Real-Time Detection of Sodium in Interstitial Fluids - Zheng, Youbin (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.